The Influence of Greenwashing on Green Trust with Green Consumer Confusion and Green Perceived Risk as Mediating Variables: A Case Study of Aqua Mineral Water - Najwa Ummi Alfauzziyah; Misbak; Tiara Muthiarsih (Mabsya: Jurnal Manajemen Bisnis Syariah, 2026)
This study investigates the effect of greenwashing on green trust, with green consumer confusion and green perceived risk as mediating variables, using AQUA mineral water as the case study. Motivated by rising consumer environmental awareness, companies have increasingly adopted green marketing strategies. However, misleading or exaggerated environmental claims risk reducing consumer trust while increasing confusion and perceived risk. This quantitative study tested the proposed hypotheses using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with bootstrapping analysis, based on data collected from AQUA consumers. The findings reveal that greenwashing exerts a positive and significant direct effect on green trust. Similarly, both green consumer confusion and green perceived risk positively and significantly affect green trust. Moreover, the results confirm that green consumer confusion and green perceived risk significantly mediate the relationship between greenwashing and green trust, supporting all proposed hypotheses. Theoretically, this research enriches the sustainable marketing literature, particularly in the Indonesian context, and reinforces the relevance of Signaling Theory and Perceived Risk Theory. Practically, it provides actionable insights for companies to craft transparent and credible environmental communication strategies to foster enduring consumer trust.